Respuesta :

Answer:

1.  [tex]y = 3x -1[/tex]

2. [tex]y = -2x - 2[/tex]

3.  [tex]y = -x - 4[/tex]

Step-by-step explanation:

we already know the slope of the three lines.

We know that the equation of a line is

[tex]y = mx + b[/tex]

We only need one point.

1. First graph

[tex]m = 3[/tex]

pto (1, 2)

Then the equation is:

[tex]y = 3x + b[/tex]

Now we substitute the point in the equation and clear b.

[tex]2 = 3(1) + b[/tex]

[tex]b = -1[/tex]

Finally the equation is:

[tex]y = 3x -1[/tex]

2. Second graph.

[tex]m = -2[/tex]

pto (-2, 2)

Then the equation is:

[tex]y = -2x + b[/tex]

Now we substitute the point in the equation and clear b.

[tex]2 = -2(-2) + b\\b = -2[/tex]

Finally the equation is:

[tex]y = -2x -2[/tex]

3. Third graphic

[tex]m = -1[/tex]

pto (-1, -3)

Then the equation is:

[tex]y = -x + b[/tex]

Now we substitute the point in the equation and clear b.

[tex]-3 = -1(-1) + b[/tex]

[tex]b = -4[/tex]

Finally the equation is:

[tex]y = -x - 4[/tex]